The Reasonableness of Wonder. Issue 3 (3rd July 2017) - Bendik-Keymer, Jeremy David
Abstract: Nussbaum's politics of wonder focuses on non-human animals. However, the sense of wonder within it also applies to human beings. Can wonder in Nussbaum's sense be helpful when articulating justice between people on politically liberal grounds? I argue that it can because it helps us consider our specific form of striving, that is, human freedom, in comparison and contrast with other kinds of living striving. Thereby it keeps in view striving as such. To make my case, I show how wonder in Nussbaum's sense is helpful for Rawls's core legitimation scenes of democratic fairness, the original position, and public reasoning. Furthermore, wonder is not objectionable in these scenes, since it brings into view the considerability of life, such that life should not be used without a good enough reason, on the basis of which any socialized conception of how to live well ought to proceed. Thus an environmental sensibility has a useful place within mainstream liberal justice.